Estilos de liderança e clima organizacional: um estudo comparativo - SILVA, Gesuino Carlos Caninde (Universidade Federal do Pará, 2023)
Analyzes of organizational behavior involving leadership and organizational climate provide benefits when performed in both private and public organizations. In this premise, leaders emerge in the management process, influencing their subordinates and contributing to the feeling of a collaborative climate that encourages individuals. Thus, this study investigated the perception of 129 servants working in Institutes that bring together 22 Faculties of a Higher Education Institution (HEI), regarding aspects related to leadership and the organizational climate. The specific objectives of the research were to identify leadership styles; assess the organizational climate; and relate the leadership style with the assessment of the climate. Methodologically, it was a quantitative research, of a descriptive nature, applied to IES servers, through two questionnaires adapted from previous research. To assess leadership, a questionnaire consisting of ten questions with three statements each was used, based on the leadership styles: Autocratic, Democratic and Liberal. In the climate assessment, the Support from Management factor was applied, which comprises 9 statements on a five-point Likert scale, ranging from (1) totally disagree to (5) totally agree. To relate the leadership style with the climate assessment, the Spearman Correlation Coefficient was used. As a result of the study, the Democratic leadership style was predominant (70.54%), with a positively perceived organizational climate. In the correlation between styles and climate, there was no association for the Autocratic leader; there are positive and moderate correlations for the Democratic leader; and a decline in the assessment of climate variables for the Liberal style. In conclusion, the study provides public managers with a better understanding of leadership styles and how much they can reflect, under the perception of public servants, on the organizational climate.